A study of sensorimotor reactions and vertical stability of highly qualified female athletes in aesthetic gymnastics - Bulgacheva, P.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the level of vertical stability and sensorimotor reactions (simple and complex) in masters of sports in aesthetic gymnastics [3]. Methods and structure of the study. The study was conducted at the Innovation Center of the Russian Olympic Committee (ROC) in Kislovodsk. Eight athletes from the Amouage team, members of the Russian national team, participated. Results and conclusions. This study determined the indices of simple and complex visual-motor reactions and vertical stability in highly skilled female athletes in aesthetic gymnastics. A moderate level of central nervous system activation, a predominance of excitatory processes, and good static and insufficient dynamic stability were identified.